Cannabinoid agonists inhibit neuropathic pain induced by brachial plexus avulsion in mice by affecting glial cells and MAP kinases. - Ana F Paszcuk; Rafael C Dutra; Kathryn A B S da Silva; Nara L M Quintão; Maria M Campos; João B Calixto (PLoS ONE, 2011)
Many studies have shown the antinociceptive effects of cannabinoid (CB) agonists in different models of pain. Herein, we have investigated their relevance in neuropathic pain induced by brachial plexus avulsion (BPA) in mice.Mice underwent BPA or sham surgery. The mRNA levels and protein expression of CB(1) and CB(2) receptors were assessed by RT-PCR and immunohistochemistry, respectively. The activation of glial cells, MAP kinases and transcription factors were evaluated by immunohistochemistry. The antinociceptive properties induced by cannabinoid agonists were assessed on the 5(th) and 30(th) days after surgery. We observed a marked increase in CB(1) and CB(2) receptor mRNA and protein expression in the spinal cord and dorsal root ganglion, either at the 5(th) or 30(th) day after surgery. BPA also induced a marked activation of p38 and JNK MAP kinases (on the 30(th) day), glial cells, such as microglia and astrocytes, and the transcription factors CREB and NF-κB (at the 5(th) and 30(th) days) in the spinal cord. Systemic treatment with cannabinoid agonists reduced mechanical allodynia on both the 5(th) and 30(th) days after surgery, but the greatest results were observed by using central routes of administration, especially at the 30(th) day. Treatment with WIN 55,212-2 prevented the activation of both glial cells and MAP kinases, associated with an enhancement of CREB and NF-κB activation.Our results indicate a relevant role for cannabinoid agonists in BPA, reinforcing their potential therapeutic relevance for the management of chronic pain states.